Analisis Muatan Nilai-Nilai Pendidikan Karakter dalam Buku Siswa Mata Pelajaran IPS Kelas VIII Kurikulum Merdeka Belajar - Habibi Sultan; Yunike Sulistyosari; Muhammad Faisal Lutfi Amri (Departement of Mathematics Education, 2023)
His study aims to analyze the Content of Character Education Values ​​in Student Books for Social Studies Class VIII in the Freedom to Learn Curriculum. This study uses content analysis methods and uses a qualitative research approach. In this study, the source of the data used was the Social Sciences Class VIII Student's Book of the Independent Learning Curriculum. In collecting data, it must be analyzed carefully and carefully in order to find the character education values ​​contained in the book. Based on the results of the research, the data obtained regarding the values ​​of character education contained in the Student's Books for Class VIII Social Studies Subjects of the Freedom to Learn Curriculum, namely Tolerance, Religion, Mutual Respect, Equality, Love of the Motherland, Responsibility, National Spirit, Mutual Cooperation, Critical Thinking, Competent, Competitive, Integrity, Self-starter, Discipline, Politeness, Care for the Environment, Teamwork, Friendly, Independent, Global Diversity, Mutual Respect, Curiosity, National Spirit, Social Integrity, Togetherness, Nationalism, Willing to Sacrifice , Democratic, Patriotism Spirit, Love Peace, Solidarity, and Social Care.